The Fundamental Approximation Theorem of Portfolio Analysis in terms of Means, Variances and Higher Moments - Samuelson, P. A. (Review of Economic Studies, 1970)
Journal Article The Fundamental Approximation Theorem of Portfolio Analysis in terms of Means, Variances and Higher Moments Get access Paul A. Samuelson Paul A. Samuelson Massachusetts Institute of Technology Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 37, Issue 4, October 1970, Pages 537–542, https://doi.org/10.2307/2296483 Published: 01 October 1970 Article history Received: 01 January 1970 Revision received: 01 March 1970 Published: 01 October 1970